2019
DOI: 10.1016/j.diff.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular matrix on liver stem cell fate: A dynamic relationship in health and disease

Abstract: The liver stem cell niche is a specialized and dynamic microenvironment with biomechanical and biochemical characteristics that regulate stem cell behavior. This is feasible due to the coordination of a complex network of secreted factors, small molecules, neural, blood inputs and extracellular matrix (ECM) components involved in the regulation of stem cell fate (self-renewal, survival, and differentiation into more mature phenotypes like hepatocytes and cholangiocytes). In this review, we describe and summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 95 publications
1
9
0
1
Order By: Relevance
“…The implantation of MSCs especially combined with biodegradable materials for tissue engineering applications such as collagen [ 6 , 7 ]. It is a major extracellular matrix (ECM) component that has been widely used for constructive remodeling to facilitate cell growth and differentiation [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…The implantation of MSCs especially combined with biodegradable materials for tissue engineering applications such as collagen [ 6 , 7 ]. It is a major extracellular matrix (ECM) component that has been widely used for constructive remodeling to facilitate cell growth and differentiation [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that tissue-engineered livers are an attractive organ replacement solution for compensating the shortage of liver sources. Transplanting cells into a liver matrix made up of a decellularized scaffold that mimics the microstructure of native tissues is expected to provide a functional bionic liver [21][22][23][24][25][26][27]. Our study demonstrated that detergent perfusion through the portal vein created a translucent liver matrix while maintaining the native vasculature for adequate perfusion of constructs that were able to withstand physiological blood pressures.…”
Section: Discussionmentioning
confidence: 96%
“…It is difficult to represent complex liver regeneration in vivo. In liver injury, hepatic regeneration responds to inflammatory cytokines, such as TNFα and IL-6 produced by Kupffer cells, to reconstitute the liver by rapidly inducing cells to enter the cell cycle [46,47]. Additionally, the absence of liver stem/progenitor cells, which contribute to liver regeneration, reveals the need for reinforcement in further studies [48,49].…”
Section: Discussionmentioning
confidence: 99%